Analyzing the effects of the Russian-Ukrainian war on Kenya’s agrifood systems and policy responses - Omulo, Godfrey; Mockshell, Jonathan; Mosquera, Leslie Estefany; Ritter, Thea (2023)
This policy brief examines the consequences of the Russia-Ukraine war on Kenya’s agrifood systems, focusing on its impact on food security and the country’s policy responses to counter the effects of the war. Drawing from official data, scholarly articles, institution reports, and online news sources, this brief encompasses the period from January 2019 to February 2023 to provide a nuanced understanding of the events leading up to and following the conflict. The results show that the Russia-Ukraine war resulted in high fuel and fertilizer prices in Kenya, negatively impacting overall crop productivity, agricultural sector employment, and, by extension, the entire economy. By examining data on food, fertilizer, fuel prices, inflation, and other vital indicators, this brief unravels the dynamics affecting Kenya’s agrifood systems contributing to a deeper understanding of Kenya's vulnerability to global geopolitical events. The results underscore the necessity of responsive policy strategies to ensure food security and economic resilience throughout the country.